AKAL DAN KECERDASAN DALAM PERSPEKTIF AL-QURAN DAN HADITS - Nina Arifa; Mahyuddin Barni; Ali Muammar ZA (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Intellect and intelligence have a very important position in Islam, especially in the perspective of the Qur'an and hadith. Intellect, as one of the greatest blessings given by Allah SWT to humans, becomes the main means of understanding revelation, both the Qur'an and hadith. In the Qur'an, humans are encouraged to use their intellect to contemplate the signs of Allah's greatness and understand the laws of the Shari'ah. Many verses of the Qur'an call on humans to think, reflect, and seek the truth through reason. In addition, intelligence is also emphasised as a tool to recognise the nature of life and prepare for the afterlife. The Prophet's hadith reinforces the function of reason by emphasising that true intelligence is the ability to control the passions and do charity for life after death. Islam views reason and intelligence as instruments not only for achieving intellectual knowledge, but also for building moral, spiritual awareness and obedience to Allah. Thus, reason and intelligence in the perspective of the Qur'an and hadith function as a means to seek the truth, implement Sharia, and build a balanced life between the world and the hereafter.